What constitutes a good unit trust: the Singaporean perspective - Ang, Chee Siang (2008)
This research aims to identify the factors that constitute an ideal unit trust from the Singaporean perspective in the following three aspects – risk, performance and promotion, as well as finding out the preferences of certain demographic groups of investors such as gender and income group.